International Research Publications on Education in Sri Lanka: A Scientomeric Study - Navaneethakrishnan, S.; Raja, S.; Kupeshan, R. (University of Kelaniya, 2017)
Quantitative studies of scholarly communication activities tend to have a better understanding of phenomena of construction, dissemination and use of scientific and technical knowledge. Nowadays scientometrics is considered as a standard tool of science policy and research management. It is also realized that this is the opportune time for the library professionals to study the current trend of Sri Lankan education system in the view international scholars to identify the role of the libraries in fulfilling the obligations specified in these research studies. This study was carried out with the intention to analyze the international research publications on education in Sri Lanka. The process of selection of publications was utilizing scientometric approach of research publications indexed by the web of science (WoS) database. Quantitative research methodological approach was taken, based on scientometric analysis. Results of this study shows a total of 201 publications were released by the Global scientists in education during 2010-2016 which received 4873 citations. The mean number of publications per year was 16.57%. It states that globally 9.45percents of items were from lone authors, pursued by 16.42% authors by double authors etc. 0.91 percent of collaborative author’s articles released throughout the study periods. The value of a mean RGR of publications which declined from 3.32 in 2010 to 0.32 in 2016, simultaneously the values of doubling time (Dt) of publications expanded from 0.21 in 2010 to 3.04 in 2016. The high frequency keywords were “Sri lanka” 109 (54.2%, TCLS 14, TGCS 332). The foremost cited quotation is Katulanda P, 2008, diabetic med, V25, P1062, DOI 10.1111/j.1464-5491.2008.02523.x. The suggestion of this research is to setup an enabling environment for more studies across the nations on Sri Lankan education and international researchers need to be encouraged on this.
Keywords: Scientometrics; Scholarly communication; Education